Widespread Hydration of the Back Arc and the Link to Variable Hydration of the Incoming Plate in the Lesser Antilles From Rayleigh Wave Imaging - Nicholas Harmon; Catherine A. Rychert; Saskia Goes; Benjamin Maunder; Jenny Collier; Timothy Henstock; Lloyd Lynch; Andreas Rietbrock; the VoiLA Working Group (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Subduction zone dynamics are important for a better understanding of natural hazards, plate tectonics, and the evolution of the planet. Despite this, the factors dictating the location and style of volcanism are not well‐known. Here we present Rayleigh Wave imaging of the Lesser Antilles subduction zone using the ocean bottom and land seismic data collected as a part of the VoiLA experiment. This region is an important global endmember that represents a slow (<19 mm/yr) convergence rate of old (80–120 Ma), Atlantic lithosphere formed at a slow spreading ridge. We image the fast slab, the fast‐overriding plate and the slow mantle wedge across the entire arc. We find slow velocity anomalies (∼4.1 km/s) in the mantle wedge directly beneath the arc with local minima beneath Dominica/Martinique, Montserrat and the Grenadines. We observe that slow velocities in the wedge extend 200 km into the back arc west of Martinique. The slowest mantle wedge velocity anomaly is more muted than several global wedges, likely reflecting the lower temperatures and less partial melt predicted for the Antilles. Subducted fracture zones and plate boundaries are a potential source of hydration, since they are located near the anomalies, although not directly beneath them. To match our observations, geodynamic models with a broadly hydrated mantle wedge are required, which can be achieved via deep hydration of the slab, and fluid release further into the back arc. In addition, 3‐D flow and melt migration or ponding are required to explain the shape and location of our anomalies.